Examination of Early Childhood Education in Türkiye in terms of Children's Law and Rights - KOL, Suat; TUNÇELİ, Hilal İlknur (Jurnal Cita Hukum, 2024)
Children's rights and child law have taken their current form since the second half of the 20th century. The Geneva Declaration of the Rights of the Child, published by the United Nations in 1924, aimed to secure children's rights. The primary purpose of this research is to examine early childhood education in Turkey in terms of children's rights. Childhood and the historical process of children's rights were first addressed in this context. Then, early childhood education in Turkey was examined within the framework of children's rights. The research, conducted as a literature review, revealed that Turkey participated in the 1st and 2nd Balkan Congresses in 1936 and 1938 and pioneered universal children's rights studies by contributing to the decisions made in these congresses. Additionally, the study showed that, due to the value placed on children in Turkish culture, which spans thousands of years, positive practices regarding children's rights have been carried out throughout history. Moreover, Turkey became a party to the Convention on the Rights of the Child, adopted by the United Nations General Assembly on November 20, 1989, and entered into force on September 2, 1990. It has made appropriate adjustments in its domestic law. It has been observed that, as in every stage of educational activities, early childhood education in Turkey is also conducted with a child-centred approach and in adherence to the child's legal rights. The findings obtained were discussed in the discussion section.